ANALISIS PROFITABILITAS PELANGGAN MENGGUNAKAN TIME-DRIVEN ACTIVITY-BASED COSTING (STUDI KASUS PADA HOTEL HYATT REGENCY YOGYAKARTA) - Ichwanul Kamila (ABIS: Accounting and Business Information Systems Journal, 2015)
The purpose of this study aims to investigate cost of issued hotel to serve every type consumers by using the method time-driven activity-based costing and contribution of every type the customers to hotel profit. This research is descriptive research to a draft research in the form of case studies. The study is done in Hyatt Regency Yogyakarta is one of five star hotels in Yogyakarta. The limitation of the study is for each type consumers hotel that only uses accommodation services room. Type consumers room divided into two namely transient (individuals) and group (group). The research results show that type consumers transient discount (individuals) give prosentase a profit of 53 percent of the total profit and type consumer group corporate (group) give prosentase a profit of 59% of the total the profit. Meanwhile, type consumers transient qualified (individuals) contributed 0.5% profit and type consumer group SMERF(group) in improving profitability lowest is 9%. This research are expected to provide information for the company in deciding strategy maximize the profit obtained from every consumers.